1998
DOI: 10.1172/jci1969
|View full text |Cite
|
Sign up to set email alerts
|

Anti-idiotypic antibodies prevent the serologic detection of antiribosomal P autoantibodies in healthy adults.

Abstract: A subset of SLE patients has serologically detectable autoantibodies to the ribosomal P proteins (anti-P). We reported the discovery of covert anti-P antibodies and their masking IgG-inhibitory antibodies in the sera of healthy adults. The aim of this study was to determine if these IgGinhibitory antibodies are anti-idiotypic antibodies (anti-Ids). IgG and IgG-depleted fractions of plasma from two healthy adults were assayed for inhibition of anti-P F(ab Ј ) 2 binding to the ribosomal P proteins in immunoblot.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
1
31
0
2
Order By: Relevance
“…Autoantibodies to ribosomal P proteins (anti-P) are regarded as specific for patients with systemic lupus erythematosus. Stafford and colleagues (21)(22)(23) demonstrated that in healthy individuals who tested negative for anti-P antibodies by conventional serologic screenings anti-P antibodies were in fact readily detectable after removal of the inhibitory antibodies. Similarly, autoantibodies to the E2 subunit of the pyruvate dehydrogenase complex, thought to be specific to patients with primary biliary cirrhosis, are present but inhibited by anti-Ids in healthy individuals (24).…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies to ribosomal P proteins (anti-P) are regarded as specific for patients with systemic lupus erythematosus. Stafford and colleagues (21)(22)(23) demonstrated that in healthy individuals who tested negative for anti-P antibodies by conventional serologic screenings anti-P antibodies were in fact readily detectable after removal of the inhibitory antibodies. Similarly, autoantibodies to the E2 subunit of the pyruvate dehydrogenase complex, thought to be specific to patients with primary biliary cirrhosis, are present but inhibited by anti-Ids in healthy individuals (24).…”
Section: Discussionmentioning
confidence: 99%
“…58,59 However, in spite of these mechanisms, human serum from non-diseased normal donors contains detectable levels of anti-idiotype antibody to a wide variety of autoantibodies. [60][61][62][63][64][65] Anti-idiotype antibodies are akin to anti-drug antibodies against therapeutic mAbs, that is, they are antibodies with specificity for the unique V region of other immunoglobulin molecules. The presence of autoantibodies indicates that the tolerance system is not perfect and in fact, poly-reactivity to autoantigens re-emerges during the somatic hypermutation that takes place during an immune response.…”
Section: Antibody "Immunogenicity" May Reflect Homeostasismentioning
confidence: 99%
“…38 In the latter instance, the anti-idiotypic antibodies were found to bind to anti-P F(ab) 2 from both lupus patients and healthy adults. 39 Although normal sera contained anti-idiotypic antibody to anti-PDC-E2, such sera failed to inhibit binding between HRP-conjugated anti-PDC-E2 and PDC-E2, suggesting that anti-idiotypic antibodies (Ab2) in normal sera do not react with the paratope, but rather with other regions on the framework of F(ab) 2 (Ab1). Alternatively, the lack of blocking could be explained by a much stronger binding affinity between PDC-E2 and anti-PDC-E2 (Ab1) in PBC serum than between anti-PDC-E2 (Ab1) and anti-idiotypic antibody (Ab2) in normal serum.…”
Section: Discussionmentioning
confidence: 98%